Motivational climate, goal orientation, perceived sport ability, and enjoyment within Finnish junior ice hockey players - Jaakkola, T.; Ntoumanis, N.; Liukkonen, J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The aim of this study was to investigate the relations among situational motivational climate, dispositional approach and avoidance achievement goals, perceived sport ability, and enjoyment in Finnish male junior ice hockey players. The sample comprised 265 junior B-level male players with a mean age of 17.03 years (SD?=?0.63). Players filled questionnaires tapping their perceptions of coach motivational climate, achievement goals, perceived sport ability, and enjoyment. For the statistical analysis, players were divided into high and low perceived sport ability groups. Multigroup structural equation modeling (SEM) revealed an indirect path from task-involving motivational climate via task-approach goal to enjoyment. Additionally, SEM demonstrated four other direct associations, which existed in both perceived ability groups: from ego-involving motivational climate to ego-approach and ego-avoidance goals; from ego-approach goal to ego-avoidance goal; and from task-avoidance goal to ego-avoidance goal. Additionally, in the high perceived sport ability group, there was an association from task-involving motivational climate to enjoyment. The results of this study reveal that motivational climate emphasizing effort, personal development and improvement, and achievement goal mastering tasks are significant elements of enjoyment in junior ice hockey.